A medium-term assessment of efficacy in surgical treatment of female stress urinary incontinence with the retropubic and transobturator approach - Szymański, Jacek; Siekierski, Paweł B.; Baranowski, Włodzimierz (Menopause Review/Przegląd Menopauzalny, 2008)
The aim of the study was to assess intra-operative complications, early postoperative complications and efficacy of two methods used for treatment of female stress urinary incontinence. The analysis involved 91 TVT (tension free vaginal tape) and 60 TOT (transobturator tape) procedures. Preoperative patient assessment included medical history, physical and gynaecological examination with cough test, prolapse evaluation according to the POPQ scale, pad test and urodynamic testing. The patient self-assessed efficacy evaluation was based on interviews during follow-up visits, as well as use of IIQ-7 and VAS questionnaires, completed before surgery and 6 months after the procedure. The groups were comparable in terms of patient characteristics, urodynamic results and preoperative quality of life. The time of the TOT procedure was significantly shorter than TVT (median 20 min vs. 35 min, p=0.0001). The average intra-operative blood loss was significantly lower for the TOT procedure (p=0.006). The hospitalisation time in both groups was comparable (median 3 days, p=0.08). Bladder perforation was only seen during TVT procedures and occurred in 5% of cases. Postoperative urination difficulties occurred in 13% of TVT patients and 5% of TOT patients. A significantly lower risk of intra-operative and early postoperative complications was noted in TOT patients, as compared to those undergoing TVT (OR=0.35%, 95% CI 0.13–0.92). A similar cure rate was observed in both groups (p=0.32; 88% after TVT, 95% after TOT), as well as improvement (2% after TVT and 2% after TOT) and failure rates (10% after TVT, 3% after TOT). TVT and TOT procedures are characterised by a high cure rate. However, it seems that, due to the reduced risk of complications, shorter procedure time and lower intra-operative blood loss, the transobturator approach should be the preferred method of SUI treatment.